2021
DOI: 10.3390/pathogens10091184
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Immunodiagnostic Tests for Typhoid Fever: A Systematic Review and Meta-Analysis

Abstract: Typhoid fever, also known as typhoid, is a life-threatening bacterial infection that remains a global health concern. The infection is associated with a significant morbidity and mortality rate, resulting in an urgent need for specific and rapid detection tests to aid prevention and management of the disease. The present review aims to assess the specificity and sensitivity of the available literature on the immunodiagnostics of typhoid fever. A literature search was conducted using three databases (PubMed, Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Various serological tests have been reported in literature using speci c antigenic protein for the diagnosis of typhoid fever. However, the performance of the tests was inadequate and the positive predictive value of these tests are the major drawbacks in diagnosis of typhoid fever 22 . These previous reports have revealed the immunodiagnostic gap which led to under and inaccurate diagnosis of typhoid fever.…”
Section: Discussionmentioning
confidence: 99%
“…Various serological tests have been reported in literature using speci c antigenic protein for the diagnosis of typhoid fever. However, the performance of the tests was inadequate and the positive predictive value of these tests are the major drawbacks in diagnosis of typhoid fever 22 . These previous reports have revealed the immunodiagnostic gap which led to under and inaccurate diagnosis of typhoid fever.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the presence of antibodies in blood does not always correlate with bacteraemia. Antibodies are known to persist in the body for several months, even years, posing a challenge in distinguishing between acute and chronic infections [29]. A study that looked at antibody decay profiles, found that IgG antibodies could persist in blood for over a year, whilst IgM levels appeared to decline after 3 to 4 months [30].…”
Section: Discussionmentioning
confidence: 99%
“…It showed moderate sensitivity and specificity of 56-84% and 31-97% respectively [62]. None of them yielded satisfactory results when tested in high-burden countries [64]. Although cheap and simple, clinicians in lowresource endemic settings should cautiously rely on them as early diagnostic tools.…”
Section: Non-culture-based Techniquesmentioning
confidence: 99%